2003
DOI: 10.1093/jn/133.11.3941s
|View full text |Cite
|
Sign up to set email alerts
|

Animal Source Foods Improve Dietary Quality, Micronutrient Status, Growth and Cognitive Function in Kenyan School Children: Background, Study Design and Baseline Findings

Abstract: A previous longitudinal three-country study in Egypt, Kenya and Mexico found significant positive associations between intake of animal source foods (ASF) and growth, cognitive development and physical activity. To test for a causal relationship, a controlled school feeding intervention study was designed to test the hypotheses that ASF would improve micronutrient status, growth and cognitive function in Kenyan primary school children. Twelve rural Kenyan schools with 554 children were randomized to four feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
234
1
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(257 citation statements)
references
References 25 publications
5
234
1
12
Order By: Relevance
“…The results showed that 96?9 % of infants in the intervention group were fed meats or organ meats at age 12 months, nearly double that reported by the control group (58?2 %). Findings from previous observational and randomised controlled studies have shown positive effects of animal-source foods on child growth and cognitive development (22)(23)(24)(25) , and therefore researchers have advocated the use of animal-source food to address maternal and child malnutrition problems in developing countries (26) . In October 2008, the WHO re-emphasised the role of the animalsource foods as 'the first and most effective choice to treat moderately malnourished children' (27) .…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that 96?9 % of infants in the intervention group were fed meats or organ meats at age 12 months, nearly double that reported by the control group (58?2 %). Findings from previous observational and randomised controlled studies have shown positive effects of animal-source foods on child growth and cognitive development (22)(23)(24)(25) , and therefore researchers have advocated the use of animal-source food to address maternal and child malnutrition problems in developing countries (26) . In October 2008, the WHO re-emphasised the role of the animalsource foods as 'the first and most effective choice to treat moderately malnourished children' (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of even small amounts of animal source foods has been shown to contribute substantially to ensuring dietary adequacy and preventing undernutrition and nutritional deficiencies (Neumann et al, 2003). Extensive longitudinal studies in Egypt, Kenya and Mexico (Neumann et al, 2003) have shown strong associations between intake of animal source foods and better growth, cognitive function and physical activity of children, better pregnancy outcomes and reduced morbidity from illness.…”
Section: Livestock and Nutritionmentioning
confidence: 99%
“…Extensive longitudinal studies in Egypt, Kenya and Mexico (Neumann et al, 2003) have shown strong associations between intake of animal source foods and better growth, cognitive function and physical activity of children, better pregnancy outcomes and reduced morbidity from illness. Consumption of adequate amounts of micronutrients, such as those that can be found in animal source foods, is associated with more competent immune systems and better immune responses (Keusch and Farthing, 1986).…”
Section: Livestock and Nutritionmentioning
confidence: 99%
“…The projected increase in meat consumption is a sign of a better future with regard to malnutrition levels among the poor in lower‐income countries who suffer from micronutrient deficiencies and mainly depend on high fiber and phytate plant‐based staples (Neumann et al., 2003). The impact of malnutrition is globally estimated to be as high as US$3.5 trillion per year or US$500 per individual (FAO, 2013).…”
Section: Introductionmentioning
confidence: 99%